A dimension five Lorentz-violating nonminimal coupling for mesons in the KLZ model - Mouchrek-Santos, V. E.; Ferreira, Manoel M.; Miller, Carlisson [UNESP] (Elsevier B.V., 2019)
We investigate a dimension five Lorentz-violating (LV) nonminimal coupling between the neutral vector meson field strength and the pion current in the context of the Kroll-Lee-Zumino (KLZ) model. In this modified model we study the vector meson dominance (VMD) by means of the imposition of new universality conditions between the couplings that comes from LV contributions. We also show that the LV nonminimal coupling leads to a linear momentum dependence in the timelike pion form factor, that is used to evaluate LV corrections for the muon anomalous magnetic moment. The experimental imprecision of such a quantity allows us to obtain upper bound (g) over bar xi(0) < 1.0 GeV-1. In addition, we also use the LV nonminimal coupling in the KLZ model to recalculate the rho decay rate. In this case the experimental imprecision is used to constrain the magnitude of the LV parameter at the level of (g) over bar xi(0) < 1.9 x 10(-2) GeV-1. (C) 2019 The Author(s). Published by Elsevier B.V.